Ziyadah Dalam Transaksi S-Paylater di Aplikasi Shopee Perspektif Maqasidus Syari’ah - Fathul Qorib; Nawawi Nawawi; Moh. Mahrus (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2023)
S-Paylater is one of Shopee's sought-after features because it allows Shopee users to purchase items whenever desired without immediately burdening their financial condition. Essentially, users buy items on Shopee and pay for them at a later date, often phrased as 'buy now, pay later.' However, in practice, S-Paylater entails certain additional fees or interest ('ziyadah'), causing the prices of items through Paylater to be higher compared to cash purchases. Consequently, the legality of S-Paylater has sparked considerable debate among scholars. This article aims to bridge that debate by examining and assessing each instance of 'ziyadah' in S-Paylater transactions. The research conducted falls within the realm of qualitative field research, utilizing the Maqasid Shariah theory. The research findings indicate three types of 'ziyadah' in S-Paylater transactions: a 1% 'ziyadah' and an approximately 2.95% 'ziyadah,' both of which are considered permissible as they align with Shariah principles such as mutual consent, absence of speculation, and the absence of riba. However, a 5% 'ziyadah' imposed as a late fee is deemed impermissible due to its violation of Shariah principles, specifically riba. Nevertheless, instances of this late fee are rare and avoidable. Therefore, fundamentally, the practice of S-Paylater constitutes a legal and permissible transaction.